Survey of Text Plagiarism Detection - Ahmed Hamza Osman; Naomie Salim; Albaraa Abuobieda (Computer Engineering and Applications Journal (ComEngApp), 2012)
In this paper we are going to review and list the advantages and limitations of the significant effective techniques employed or developed in text plagiarism detection. It was found that many of the proposed methods for plagiarism detection have a weakness and lacking for detecting some types of plagiarized text. This paper discussed several important issues in plagiarism detection such as; plagiarism detection Tasks, plagiarism detection process and some of the current plagiarism detection techniques.